Resource use and conflict in Phu Khieo Wildlife Sanctuary, Thailand : a case study on people - park interaction - Pornpita Khlangpukhiaw; Rajendra Shrestha; Ganesh Shivakoti; Soparth Pongquan; Ford Foundation International Fellowships Program (IFP); Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
The purpose of this study was to explore the conflict between the local people and Phu Khieo Wildlife Sanctuary in term of natural resources use. Therefore, the specific objectives are to: 1) identify the natural resources use pattern of the local people communities and assess the level of dependency on natural resources of PKWS; 2) to assess the cause and type of conflict; 3) to examine the impact and degree of the conflict; 4) to document the dynamic of the few households; 4) to examine the conflict management at the household, and community; and 5) to examine the conflict management at the household, and community level. This study was conducted in two villages surrounding PKWS in Northeastern of Thailand. In order to obtain essential information for its analysis, questionnaires, interviews and group discussion were applied during data collection. The result of this study indicates that most villagers consider the natural resources especially NTFPs of PKWS as their important livelihood base. They gathered and collected various kinds of NTFPs for direct home consumption and for household income especially bamboo shoot, fish, and edible vegetables. There were three main causes of conflict which were unbalance benefits, different in view, and resources scarcity mainly fish scarcity. The two major types of conflict in the study area were active conflict and passive conflict. The actions of those conflicts were occurred in different period of time and group of people. The result of the conflict influences to both individual level and community level. The bad relationship brings non-cooperation to both sides and can cause of personal danger, and non-developed community. However, the degree of conflict transfers and transforms by the role of time. In the past, the local respected people solved the conflicts, whereas the conflicts manage by the court at the present time. However, to avoid the court, both sides handle the conflict by avoidance each other.
A thesis submitted in partial fulfillment of the re quirements for the degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Phu Khieo Wildlife Sanctuary (Thailand); Wildlife refuges -- Public use -- Thailand